The reality of administrative creativity of secondary schools' managers in Al-zarqaa province (Journal Of Educational and Psychological Researches, 2018)
The study focuses on identifying the reality of administrative creativity of secondary schools' managers in Al-zarqaa province. The descriptive approach was adopted to conduct this study. To achieve the study objective, the author designed a questionnaire composed of (24) items included (4) domains applied on (80) male and female school managers were selected randomly. The results showed that the administrative creativity level of secondary school's managers over all domains were too high which ranked as school management domain followed by public community domain then teacher domain and finally, school environment domain. Additionally, each of male, private sector, and experience over 10 years revealed significant differences.